AROMATHERAPY AS A NON-PHARMACOLOGICAL INTERVENTION FOR ANXIETY REDUCTION IN UNIVERSITY STUDENTS: A LITERATURE REVIEW - Delvi Jasyanti; Abdullah, Dessy; Betty Fitriyasti (Nusantara Hasana Journal, 2025)
University students face various psychological challenges, one of which is anxiety. Anxiety can interfere with their academic performance and daily activities. Non-pharmacological therapies, such as aromatherapy, have been explored as potential treatments for reducing anxiety. This study employs a literature review approach to examine the impact of aromatherapy on anxiety reduction among university students. Articles were collected using Google Scholar, following the PICO-S framework. The review included studies published in the last five years in Indonesian, focusing on the effects of aromatherapy on anxiety in students. A total of six studies were selected, and all indicated that aromatherapy had a significant effect in reducing anxiety levels in university students. Essential oils such as lavender and peppermint were commonly used and showed positive outcomes. Aromatherapy is an effective non-pharmacological intervention for anxiety, providing an alternative to pharmacological treatments. The results suggest that essential oils can help alleviate the stress and anxiety caused by academic pressures, with lavender and peppermint being particularly effective. Further research is recommended to explore the long-term effects and other essential oils in this context. Aromatherapy has been proven to be an effective therapy for reducing anxiety in university students, offering a natural, side-effect-free alternative to medication.